Services and the GATT - Siegried Schultz (Intereconomics, 1987)
The Uruguay Round of the GATT represents a test of the adaptability and reformability of the multilateral trading system. This is particularly true with regard to trade in services, the treatment of which within GATT has been resisted (to varying degrees) by many developing countries. The following two articles deal with different aspects of this issue.
Keywords: 330; International Trade